The Effect of Financial Literacy and Access to Capital on MSME Performance through Financial Management - Noprian; Darman; Moh Ryan YL Saad (Universitas Bina Mandiri Gorontalo, 2026)
While MSMEs are pivotal to regional economic expansion, their growth is often impeded by poor financial literacy, funding constraints, and suboptimal financial management. This quantitative study investigates the influence of financial literacy and capital access on MSME performance in Gorontalo Province, positioning financial management as a mediating variable. Data from 52 purposively sampled MSME owners were analyzed using SEM-PLS via SmartPLS 4.0. The findings indicate that both financial literacy (βbeta = 0.661, p < 0.001) and access to capital (βbeta = 0.296, p = 0.013) significantly and positively impact financial management. Consequently, financial management strongly enhances MSME performance (βbeta = 0.711, p < 0.001). Interestingly, financial literacy and capital access yield no significant direct effect on performance. Crucially, financial management fully mediates the impact of financial literacy (βbeta = 0.470, p < 0.001) and capital access (βbeta = 0.211, p = 0.040) on business performance. The novelty of this research underscores financial management as a vital bridging mechanism in Gorontalo, demonstrating that business success relies more heavily on structural budgeting capabilities rather than merely possessing financial knowledge or capital resources.